What Are Scenarios Telling Us About Developing Climate-Resilient Pathways in the Southern African Region? - Lipper, Leslie (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Over the past 10 years, there have been a myriad of foresight exercises and scenarios developed that are relevant to consider in the context of building climate-resilient pathways of development in the SADC region. These scenarios consider different pathways for developing climate-resilient food and agricultural systems relevant for the region. However, not all the scenarios ar e developed for the r egion; most are either at SSA or country level, with a few at regional level, and several at global level.